Identify the prevention barriers in the steam boiler incident causation processes - Ngadiman, Siti Suraya (2018)
Promising accident modelling is becoming challenging with the growing complexity of the risky process activity. The objectives of this research are to identify the safety prevention barriers in the boiler incident causation process and to assess the plausible hazards and root causes of the boiler accident in the processing industry. The data of the boiler incident are collected through the Past Accident Analysis (PAA) to determine the accident contributors and sub accident contributors. The Fault Tree Analysis (FTA) is used to calculate the failure probability of the proposed prevention barriers based on dependency of the accident contributors and sub accident contributors. The Event Tree Analysis (ETA) is applicable to predict the consequence from the causes of the accident contributors and also to calculate the successful of the proposed prevention barriers. As conclusion, the combination of the FTA and ETA are providing an overall illustration of boiler incident process. In this study, the prevention barriers in the steam boiler incident are determined.